Cultural Invasion in the Javanese Language on Social Media - Sholihah, Rizki Amalia; Ma'ruf, Amir; Munandar, Aris (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This paper aims to complement the shortcomings of previous studies by examining the existence of cultural invasion in general, namely by selecting specific communities, in this case, the Ponorogo Regency, for the use of regional languages and social media as the focus of the discussion. This paper is based on the argument that the cultural invasion also penetrated the regional languages as part of the culture with the means of shifting, namely on social media. Through a survey method conducted on the people of Ponorogo Regency to fill out a questionnaire about the use of language on social media, it was found that the respondents actively used social media consisting of social networking, namely Facebook and Twitter, photo sharing, namely Instagram, and interactive media, namely TikTok. This data collection was carried out within three months, from July to September 2022. All respondents used social media to use Indonesian and foreign languages. Of all the respondents, apart from using this language, 28 respondents also used Javanese. Another 72 respondents only use Indonesian and foreign languages when surfing social media. However, compared to foreign languages, the number of Javanese users on social media is still more significant. This shows that cultural invasion did occur in Ponorogo, namely with the Javanese language, which experienced a shift from the primary language in communication because more people used Indonesian as the national language. In addition, the increasing use of foreign languages in social media shows symptoms of an even greater cultural invasion.